Research on harmonics reduction of Samsung Display Vietnam industrial park - Nguyễn Quốc Minh; Nguyễn Quang Thắng; Đoàn Văn Minh (Journal of Military Science and Technology, 2022)
Samsung Display Vietnam (SDV) is a Samsung Group FDI company located in Yen Phong Industrial Park, Bac Ninh Province, specializing in the production of screen electronic components. This factory has a production line with a high degree of automation, using a lot of nonlinear loads as well as electronic devices capable of causing large harmonics such as single-phase inverters, motor controllers, robot controller, uninterruptible power supply unit (UPS), etc. Actual operation recorded the harmonic level at some 0.4 kV busbars in the factory reached over 60%, violating the regulations on harmonic standards provided by EVN’s distribution grid code, severly affecting the power quality of the distribution sytem. This article will focus on assessing the harmonics level in the Samsung Display Vietnam Industrial Park, and research on solutions to reduce the harmonics level to the standard requirement. Simulation results were performed on Electrical Transient Analyzer Program (ETAP) software.